Nothing new under the sun: The so-called "growth model perspective" - Bruno Amable (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
Recent contributions in comparative political economy have made much of the 'growth model perspective', presenting it as a way to 'rethink political economy'. This paper argues that the origins of the growth model approach can be found in contributions by Michel Freyssenet made in the framework of GERPISA (Groupe d'étude et de recherche permanent sur l'industrie et les salariés de l'automobile) in the 1990s/2000. By presenting the contributions and limitations of Freyssenet's approach, it is possible to establish how contemporary growth model approaches fail to establish a solid link between political economy and heterodox macroeconomics. It appears that an approach that starts from the differentiation of interests of social groups and takes into account the autonomy of politics has more potential to achieve this task, allowing to recover the inspiration of Kalecki's 1943 article on the political limits to economic policy.
Keywords: B52; P10; 330; French Theory of Régulation; growth models; accumulation regimes; political economy